Alphabeep : a zipping, zooming ABC - Pearson, Debora; Miller, Edward, 1964- (New York : Holiday House, 2003)
Describes a vehicle or street sign for every letter of the alphabet from Ambulance to Zamboni.
JP mc
Keywords: Motor vehicles -- Juvenile literature; English language -- Alphabet -- Juvenile literature; Vehicles -- Juvenile literature; Traffic signs and signals -- Juvenile literature; Alphabet books; Preschool picture book